SPIDAR activity at the ASC - Nihill, G. (Ausport, 2006)
When Claire Short talks about Spidarman (and she does so, often), it is important to understand that she is not referring to the red and blue tights-wearing comic book cum movie hero. Short, who is the Audio Visual Services Manager at the Australian Sports Commission`s (ASC`s) National Sport Information Centre, is actually talking about SPIDAR — the acronym for Sports Performance Information and Digital Asset Repository.